Non-apoptotic functions of caspase-7 during osteogenesis - Svandova, E; Lesot, H; Vanden Berghe, T; Tucker, A S; Sharpe, P T; Vandenabeele, P; Matalova, E (Cell death & disease, 2014)
Caspase-3 and -7 are generally known for their central role in the execution of apoptosis. However, their function is not limited to apoptosis and under specific conditions activation has been linked to proliferation or differentiation of specialised cell types. In the present study, we followed the localisation of the activated form of caspase-7 during intramembranous (alveolar and mandibular bones) and endochondral (long bones of limbs) ossification in mice. In both bone types, the activated form of caspase-7 was detected from the beginning of ossification during embryonic development and persisted postnatally. The bone status was investigated by microCT in both wild-type and caspase-7-deficient adult mice. Intramembranous bone in mutant mice displayed a statistically significant decrease in volume while the mineral density was not altered. Conversely, endochondral bone showed constant volume but a significant decrease in mineral density in caspase-7 knock-out mice. Cleaved caspase-7 was present in a number of cells that did not show signs of apoptosis. PCR array analysis of the mandibular bone of caspase-7-deficient versus wild-type mice pointed to a significant decrease in mRNA levels for Msx1 and Smad1 in early bone formation. These observations might explain the decrease in the alveolar bone volume of adult knock-out mice. In conclusion, this study is the first to report a non-apoptotic function of caspase-7 in osteogenesis and also demonstrates further specificities in endochondral versus intramembranous ossification.
Keywords: Smad1 Protein; osteokalcin; kosti a kostní tkáň; počítačová rentgenová tomografie; Caspase 3; Mice, Knockout; kaspasa 3; osteogeneze; Embryonic Development; protein Smad1; Caspase 7; MSX1 Transcription Factor; myši knockoutované; Tomography, X-Ray Computed; Animals; kaspasa 7; zvířata; embryonální vývoj; myši; apoptóza; Osteocalcin; Osteogenesis; Mice; transkripční faktor MSX1; Bone and Bones; Apoptosis